Patrimônio histórico e turismo na cidade de Veranópolis/RS - Comarú, Itamar Ferretto (My University, 2014)
Broke with the goal of developing a study that involved three main themes: Tourism, History and Memory. The three themes are related in search of a study which may contribute to the enhancement of urban landscapes as tourist attractions, recognizing the city or its urban centers, as permeated by cultural relationships that involve multiple fields and interests. Thus, this study aimed to analyze and understand the relationships between tourism, Memories and the City, with the eyes on the location of Veranópolis. Whereas the city and its image are the result of practices and representations of social groups, urban areas become attractive tourism representative for the cities, given that there are visible the different times and presenting the stories of Thus, streets and squares articulate these temporalities between the groups, which may support an attraction for visitors. It can be seen in Veranópolis, a distance between tourism and the city, such as urbanity. Looking at the image of tourism advertised, as well as records related to the activity, it is clear that the option for natural has a long history. But at other times at the beginning of the twentieth century, which was posted were just the city and its cultural attractions, which points to an ominous reductionism of local tourism, the distance between Tourism and the City, giving great emphasis to nature existing in the locality, which seems to be a reductionist approach to local tourism.
Partiu-se com o objetivo de desenvolver um estudo que envolvesse três temáticas principais: Turismo, História e Memória. As três temáticas se relacionam na busca de um estudo que possa contribuir para a valorização das paisagens urbanas como atrativos turísticos, reconhecendo a cidade, ou seus centros urbanos, como bens culturais permeados por relações que envolvem múltiplos campos e interesses. Sendo assim, este estudo teve como principal objetivo analisar e compreender as relações entre Turismo, Memória e Cidade, com o olhar voltado para a localidade de Veranópolis/RS. Considerando que a cidade e sua imagem são frutos das práticas e representações dos grupos sociais, os espaços urbanos tornam-se representativos atrativos turísticos para as localidades, tendo em vista que ali se encontram visíveis as diversas temporalidades que apresentam as histórias da localidade. Assim, ruas e praças articulam essas temporalidades entre os grupos, podendo servir como suporte de atração para visitantes. Percebe-se, em Veranópolis, um distanciamento entre turismo e cidade, como urbanidade. Analisando a imagem turística propagandeada, assim como os registros relacionados à atividade, percebe-se que a opção pelo natural vem de longa data. Porém, em outros tempos, no princípio do século XX, o que era destacado eram justamente a cidade e seus atrativos culturais, o que aponta para um nefasto reducionismo da atividade turística local, pelo distanciamento entre Turismo e Cidade, dando-se grande ênfase à natureza existente na localidade, o que parece ser uma atitude reducionista à atividade turística local.
Keywords: TURISMO; Turismo; Cidades; Patrimônio cultural; Região; Veranópolis/RS; Tourism; Cities; Heritage sites; Region; Veranópolis/RS